CGIAR Research Program on Policies, Institutions, and Markets - Plan of Work and Budget 2021 - CGIAR Research Program on Policies, Institutions, and Markets (CGIAR Research Program on Policies, Institutions, and Markets, 2021)
The CGIAR Research Program on Policies, Institutions, and Markets (PIM) is led by the International Food Policy Research Institute (IFPRI) and brings together 15 CGIAR centers and many partners. External managing partners include KIT Royal Tropical Institute, Michigan State University (MSU), University of Oxford, Wageningen University and Research (WUR), and World Vision International.